Tanggung Jawab Penyedia Layanan Kesehatan Aplikasi Pedulilindungi terhadap Keamanan Data Pribadi Konsumen - Ni Kadek Marantina Dewi; I Nyoman Putu Budiartha; I Nyoman Subamia (Warmadewa Press, 2022)
One proof that someone has been vaccinated is with a certificate that can be seen through the PeduliLindung application. However, there were complaints from a number of people regarding the issue of leaking personal data in the PeduliLindungi application, making the public less sure of the effectiveness of the application. Thus, this research aims to discuss the regulations and policies of the government for the protection of personal data and what is the responsibility of the PeduliLindung application service provider for the data of a consumer in health services. The research method used is the normative method. The approach used is a statutory approach and a conceptual approach. The main material of this research is legislation related to the cases raised in this research, while the supporting materials are books and legal journals that are relevant to the research. The results of this research show that personal data contained in the Cares Protect application includes name, date of birth, complete address, gender, and nationality. In various countries, special rules have been formulated regarding the protection of personal data, but so far Indonesia does not have such regulations. This issue is only regulated in Article 26 of the ITE Law. It is hoped that the government will soon enact a bill on PDP in Indonesia. So that later it can provide a deterrent effect and minimize the illegal spread of personal data in the PeduliLindungi application.